A comprehensive study on the largest amplitude traceable short gravimetric calibration line in China - Liu, Zhenghua; Gou, Jianing; Li, Ji; Hu, Junjie; Zhang, Xin (Frontiers in Earth Science, 2025)
Relative gravimeter must be calibrated periodically on a gravimetric calibration line with a tiny uncertainty. We created a new gravimetric calibration baseline with a 326 milligal gravity difference in Jiugong Mountain, central China. The baseline consisted of four absolute gravimetry stations and eight basic relative gravimetry stations. Firstly, we carried out metrological parameters calibration (laser length and atomic clock) for FG5X(#265) and A10(#057) gravimeter with beat frequency experiment and atomic clock comparison respectively. Then we compared absolute gravity measurement from A10#057 and FG5X#265. We obtained a normalized error (i.e., the ratio of the gravity difference over the expended uncertainty of the difference) of 0.58, indicating that the discrepancy between both measurements lies within the measurement uncertainties. In order to precisely characterize the 4 absolute gravity stations, we conducted i) vertical and horizontal gravity gradients, and ii) we estimated the seismic background noise level. Finally, we have conducted relative gravimetric survey using Scincrex CG6(#236 and #238) constrained by FG5X and A10 absolute gravimeter to fulfill metrological traceability of the calibration line. The findings show that the basic relative station’s and absolute stations’ respective errors on the gravitational acceleration are 3 μGal and 5 μGal. For each gravity difference, the average biases between the FG5X-265 and CG-6 gravimeter are included in the uncertainty of the absolute observations.